Challenges in Diagnosing Narcolepsy and Idiopathic Hypersomnia - Seung-Chul Hong; Ji Hyun Song; Tae-Won Kim; Young-Chan Kim (Sleep Medicine Research, 2023)
Narcolepsy and idiopathic hypersomnia are central disorders of hypersomnolence accompanied by excessive daytime sleepiness, which are not caused by nocturnal sleep disturbance, sleep deficiency, or circadian rhythm sleep disorders. Several studies have questioned the repeatability of the Multiple Sleep Latency Test (MSLT) in type 2 narcolepsy (NT2) patients. After two or more repeated MSLTs, the diagnosis of type 1 narcolepsy (NT1) is maintained in more than 90% of cases, while only half of the NT2 patients retain their original diagnosis. The diagnosis of NT2 may shift to idiopathic hypersomnia based on the MSLT results, making the differential diagnosis of NT2 and idiopathic hypersomnia particularly challenging. Therefore, this study suggests the need for new tests in addition to the MSLT for diagnostic consistency in NT2 and idiopathic hypersomnia.